2014
DOI: 10.3171/2013.10.jns13332
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamotomy in the treatment of Parkinson's disease: clinical aspects and mechanisms of action

Abstract: Parkinson's disease (PD) is a neurodegenerative condition that can be pharmacologically treated with levodopa. However, important motor and nonmotor symptoms appear with its long-term use. The subthalamic nucleus (STN) is known to be involved in the pathophysiology of PD and to contribute to levodopa-induced complications. Surgery is considered in patients who have advanced PD that is refractory to pharmacotherapy and who display disabling dyskinesia. Deep brain stimulation of the STN is currently the main sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 177 publications
2
18
0
1
Order By: Relevance
“…Even though it shows similar efficacy and possible benefits over pallidotomy [47,48], there is a well-known chance of permanent hemiballism as a consequence of the surgery. In this regard, Alvarez et al demonstrated in their series that 15% of the patients developed postoperative hemichorea-ballism [49].…”
Section: ) Efficacy and Safety Of Pallidotomy Vs Dbsmentioning
confidence: 91%
“…Even though it shows similar efficacy and possible benefits over pallidotomy [47,48], there is a well-known chance of permanent hemiballism as a consequence of the surgery. In this regard, Alvarez et al demonstrated in their series that 15% of the patients developed postoperative hemichorea-ballism [49].…”
Section: ) Efficacy and Safety Of Pallidotomy Vs Dbsmentioning
confidence: 91%
“…Subthalamotomy abolishes the overactive subthalamopallidal excitatory outflow (Bergman et al, 1994) and that results in motor improvements in PD patients in both "ONmedication" and "OFF-medication" states (Jourdain et al, 2014). Furthermore, PD patients may see their dopaminergic medication reduced by 45% in the first year and 30% after two years (Jourdain et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Subthalamotomy abolishes the overactive subthalamopallidal excitatory outflow (Bergman et al, 1994) and that results in motor improvements in PD patients in both "ONmedication" and "OFF-medication" states (Jourdain et al, 2014). Furthermore, PD patients may see their dopaminergic medication reduced by 45% in the first year and 30% after two years (Jourdain et al, 2014). When keeping the same L-DOPA daily dose after subthalamotomy, patients had a better motor response and spent more time "ON-medication", indicative of a beneficial effect on wearing-off (Alvarez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Side effects from unilateral STN ablation can include hemiballismus/hemichorea and postural instability, though these are typically transient. 27 The effects of FUS on the STN are unclear at this time but multiple trials are currently under way to explore this (ClinicalTrials.gov Identifiers: NCT02003248 and NCT02252380). As of yet, there are no published preliminary data from these studies available.…”
Section: Subthalamic Nucleusmentioning
confidence: 99%